On diversity performance of two-element coupling element based antenna structure for mobile terminal - Azremi, Abdullah Al Hadi; Toivanen, J.; Laitinen, J.; Vainikainen, P.; Chen, X.; Jamaly, N.; Carlsson, J.; Kildal, P.-S. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/